ANALISIS IKLAN KESEHATAN PADA KORAN BINTANG BORNEO TAHUN 1930 - Rizal Izmi Kusumawijaya; Ramadani, Jerry; Muhammad Azmi (Amarthapura: Historical Studies Journal, 2022)
The health needs of the community are utilized by health service entrepreneursadvertise their health services in the mass media. Advertisements offering health services are increasingly widespread in print media, local radio and television. In the print media themselves, they generally advertise in the form of classified ads or (mini-ads) which are relatively cheap. The number of advertisements every day or every month is different in certain newspapers. There are quite a lot of advertisers offering various medical services such as alternative medicine, therapy, health advertisements, and so on. The author uses a case study method with a qualitative approach. This aims to find out the regulations or timeline of health advertisements and health service practices advertised through the Bintang Borneo newspaper in 1930, January-March. The conclusions of this research indicate that regulations or timelines relating to health advertising in mass media are not yet comprehensive. By having health advertisements in local newspapers, you can provide useful information for the local community and find out which medicines are suitable for the diseases suffered by the community.